'Florida Radiance' Strawberry - Craig K. Chandler; Bielinski M. Santos; Natalia A. Peres (EDIS)
HS-1151, a 2-page illustrated fact sheet by C.K. Chandler, B.M. Santos, and N.A. Peres, describes this short-day cultivar developed to complement the 'Strawberry Festival' for production areas in west Central Florida. Includes references. Published by the UF Department of Horticultural Sciences, December 2008.